Stand Up Comedy Indonesia as Anecdote Text Learning Media in Senior High School: Study of Critical Discourse Analysis - Ginanjar Arif Wijaya; Sarwaji Suwandi; Sumarwati Sumarwati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This research is a descriptive qualitative study that examines the relevance of social criticism on Stand Up Comedy Indonesia towards anecdotal text learning in high school. Stand Up Comedy is a form of comedy or comedy that is delivered monologically to the audience. Stand Up comedy is not only an entertaining spectacle, but every material that is aired is criticized or the message delivered. The purpose of this study was to identify the relevance of social criticism on Stand Up Comedy Indonesia towards anecdotal text learning in high school. The data in this study are in the form of a Stand Up Comedy Indonesia video. The primary data source in this study is Stand Up comedy Kompas TV documents and videos on YouTube. While secondary data sources are relevant primary books, international journals, papers, etc. that are needed in the study of theory. The data collection technique in this study is by documentation and literature. The analysis technique used in this study uses qualitative analysis techniques. Because the data obtained are in the form of texts from various different literary sources, a text analysis is needed. The results of this study are three things. 1) The discourse of stand Up comedy academy has the same structure , namely based on the genre of discourse. 2) The schema and discourse sequence of stand Up comedy academy are in accordance with anecdotal texts, namely those that have components of abstract structure, orientation, crisis, reaction and code. The division of structures can be divided into two parts, complete structure and incomplete. 3) The implementation of the results of this study can be used as teaching material at the eleventh grade high school about producing coherent anecdotal texts in accordance with the characteristics of the text made both orally and in writing.